Chlorogenic Acid-Induced Gut Microbiota Improves Metabolic Endotoxemia - Ye, Xiaolin; Liu, Yang; Hu, Jiajin; Gao, Yanyan; Ma, Yanan; Wen, Deliang (Frontiers in Endocrinology, 2021)
Background Coffee can regulate glucose homeostasis but the underlying mechanism is unclear. This study investigated the preventive and therapeutic effects of chlorogenic acid (CGA), a polyphenol that is found in coffee, on obesity and obesity-related metabolic endotoxemia. Method Male 4-week-old C57BL/6 mice were fed either normal chow or a high-fat diet or 20 weeks and half the mice in each group were gavaged with CGA. Oral glucose tolerance tests (OGTTs) and insulin tolerance tests (ITTs) were performed. Markers of inflammation and intestinal barrier function were assayed. The composition of the gut microbiota was analyzed by 16S rRNA high-throughput pyrosequencing. The role of CGA-altered microbiota in metabolic endotoxemia was verified by fecal microbiota transplantation. Results CGA protected against HFD-induced weight gain, decreased the relative weight of subcutaneous and visceral adipose, improved intestinal barrier integrity, and prevented glucose metabolic disorders and endotoxemia (P <0.05). CGA significantly changed the composition of the gut microbiota and increased the abundance of short chain fatty acid (SCFA)-producers (e.g., Dubosiella, Romboutsia, Mucispirillum, and Faecalibaculum) and Akkermansia, which can protect the intestinal barrier. In addition, mice with the CGA-altered microbiota had decreased body weight and fat content and inhibited metabolic endotoxemia. Conclusion CGA-induced changes in the gut microbiota played an important role in the inhibition of metabolic endotoxemia in HFD-fed mice.